The use of β-blockers in children in ICU – results of the interactive survey, a brief overview and own opinion - D. K. Аzovskiy; A. U. Lekmanov; A. P. Shadchnev (Вестник анестезиологии и реаниматологии, 2020)
Many hospitals use β-blockers in adult patients, however, their use in children has not yet been determined. The objective: to collect data on the use of β-blockers in children in intensive care units (ICU). Methods: an anonymous survey containing 17 questions regarding the use of β-blockers was distributed through social networks, messengers and email. The answers were compared with published data. Results. 48 respondents provided their replies. The survey has shown that 66.7% of them use β-blockers in children while 33.3% do not. Differences in the use of β-blockers in general and pediatric ICUs are statistically insignificant. Most clinics (50%) use β-blockers in patients with congenital heart defects, followed by sepsis (18.5%). Esmolol (34.4%) is the first-line drug, followed by propranolol (31.3%). The doses ranges vary significantly (excluding esmolol). Basic monitoring and echocardiography (40.6%) are most often used to monitor the use of β-blockers. Conclusion: The survey results have shown that in Russia, the use of β-blockers in children in ICU is very limited. It is necessary to conduct big randomized, multicenter, placebo-controlled studies that will determine the effectiveness of β-blockers in children in various clinical conditions.